A prática social da convivência escolar entre estudantes deficientes visuais e seus docentes: o estreito caminho em direção à inclusão - Costa, Vanderlei Balbino da (2009)
This piece of research entitled Social Practise in School Cohabit Between Blind Students And Their Teachers: The Narrow Path Towards Inclusion is the result of a work carried on between the years 2007 and 2008 in public primary schools from São Carlos, São Paulo State. In this study we found out that during decades people with disabilities have been marginalised, excluded and segregated. Thus, in this process there was no respect towards the other, the different one, the disabled. The reason for this study is that at school people with disabilities should be seen, considered, respected. In this work we sought to understand how the process of educational inclusion of regularly registered disabled students has been given in elementary and high schools of this municipality. In this scope our guiding questioning in this study was: What are the educational processes experienced by blind students in the social practise of school coexistence during compulsory education, especially in the dealings between teachers and students? The objectives of this study were: to comprehend the educational processes products of the social practise of school coexistence especially in the dealings between blind students and their teachers, particularly whether their teachers have contributed in a way that they might consider themselves as included students in the regular school teaching; and to investigate how the process of inclusion of blind students to the school regular teaching, where lessons are taught to students considered normal , has been carried out. Our methodological option in this study came to be qualitative research based on the philosophical principles of Phenomenology, which targets observation, comprehensive description of the experiences lived during the three months with the blind students and the dialogue relations between these individuals as well as with these individuals through participating observation. The proceedings were: getting close to the schools and surroundings; coexisting with these blind subjects in different educational contexts as well as in-classroom observation. Theoretical references are centred in the works of Dussel, Freire, Fiori, Brandão, among others, which made it possible for us to understand a little bit more about school education. We also made use of references which include the theme Inclusion, especially those referring to people with disabilities in the regular teaching. Finally for the Building of the Results there have been used the observations made in three of the schools of compulsory teaching, the data been systematically registered in field notes, as well as interviews with six blind students regularly registered in the schools observed. Results produced by this research led us to the conclusion that the process of Inclusion has been still carried out only in part, for we perceived the need for teacher formation, acquisition of didactic-pedagogical resources as well as adaptation of the school infrastructure to effectively receive the coming and staying of blind students to schools of São Carlos /SP.